Development Strategies for Corn Farming to Enhance Farmers’ Income in Lubuk Basung District: An Islamic Economic Perspective - Rangga Pernando; Habibatur Ridha (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to identify strategies for developing corn farming businesses to increase farmers' income in Lubuk Basung District. The research is classified as qualitative research, with a focus on understanding meaning rather than generalization. The summary of the research findings shows that corn farming businesses can apply the SO (Strengths–Opportunities) strategy to develop their businesses and achieve competitive advantages in the agricultural sector. The conclusion is that corn farming in Lubuk Basung possesses more dominant strengths and opportunities compared to weaknesses and threats.